Kepemimpinan dalam Perspektif Al-Qur'an menurut Tafsir Al-Azhar Karya Buya Hamka dan Al-Misbah Karya Quraish Shihab - Hana Af Idatul Latifah; Muswita Muswita (Tadabbur: Jurnal Integrasi Keilmuan, 2025)
Leadership is one of the central themes in the Qur’an and holds significant relevance to social, political, and religious life. Amid increasingly complex contemporary leadership challenges, including crises of integrity, abuse of power, and declining public trust in leaders, a deeper understanding of leadership grounded in Qur’anic values is urgently needed. This study aims to analyze the concept of leadership in the Qur’an through a comparative examination of QS. Al-Baqarah [2]: 30 and 124 and QS. Shad [38]: 26 as interpreted in Tafsir al-Azhar by Buya Hamka and Tafsir al-Misbah by M. Quraish Shihab. Employing a qualitative approach and library research method, the study uses the Qur’an, Tafsir al-Azhar, and Tafsir al-Misbah as primary sources, while relevant literature on Islamic leadership and Qur’anic exegesis serves as secondary data. Data were analyzed using descriptive-comparative techniques to identify similarities, differences, and the contemporary implications of both interpretations. The findings reveal that, from the Qur’anic perspective, leadership is not merely a position of authority but a divine trust that encompasses moral, spiritual, and social responsibilities. Both Hamka and Quraish Shihab emphasize three fundamental elements of leadership: human beings as khalifah (vicegerents), the earth as the sphere of stewardship, and divinely granted authority as the basis of leadership legitimacy. Furthermore, ideal leadership should be founded upon justice, trustworthiness, piety, and the ability to carry out responsibilities in accordance with divine guidance. These findings demonstrate that the Qur’anic paradigm offers an ethical model of leadership that remains highly relevant for addressing contemporary leadership challenges.